Human Psychology and Its Relation With Politics: Understanding the Role of Rationality Theories in Political Science (Journal of Advances and Scholarly Researches in Allied Education, 2014)
This article contrasts two theories of human rationality that havefound application in political science: methodical, bounded rationality fromcurrent cognitive psychology, and global, substantial rationality fromeconomics. Employing examples illustrated from the contemporary literature ofpolitical science, it analyzes the relative roles played by the rationalityprinciple and by auxiliary assumptions (e.g., assumptions about the content ofactors' goals) in explicating human behavior in political contexts, andconcludes that the mode/predictions rest originally on the auxiliaryassumptions rather than deriving from the rationality principle.